Imperative Sentences In Surah Luqman: A Study Of Structure And Meaning - Vina Ulfa Mahfudhoh; Moch. Syarif Hidayatullah; Cahya Buana (Lughawiyyat)
Structure in language is an important part, especially in Arabic. Structure is an important part of determining a meaning.This research aims to reveal the structure and meaning of imperative sentences in surah Luqman. This research is a descriptive-qualitative research. The data source used in this research is Al-Qur'an by choosing one of the surahs in it in the form of surah Luqman. The data collection method in this research uses the listening method with documentation techniques. While the data analysis method in this research uses content analysis method with semantic approach to dissect the structure and meaning. The result of this study is that the structure of imperative sentences in surah Luqman is found in the form of (1) using fi'il amr, (2) using mashdar naib 'an fi'il amr, and (3) using lām nahiy which is before fi'il muḍari'. Meanwhile, the meanings found in the imperative sentences in surah Al-Luqman are command, honour, and prohibition